A principal component analysis based three-dimensional sustainability assessment model to evaluate corporate sustainable performance. (20th June 2018) - Jiang, Qiuhong; Liu, Zhichao; Liu, Weiwei; Li, Tao; Cong, Weilong; Zhang, Hongchao; Shi, Junli
Abstract: Corporate sustainability assessment involves two procedures including quantification of the upstream/downstream impacts generated during the company's activities and integration of these impacts into a single metric. In order to achieve a desirable balance among the economic growth, environmental friendliness, and social equity, it is essential to scientifically manage and monitor the corporate sustainability. This paper proposes a three-dimensional (economic, environmental, and social) sustainability assessment model to analyze the corporate sustainable performance based on principal component analysis. An effective evaluation indicator system for cooperate sustainability assessment is provided after conducting reliability and validity analysis. Considering the coordination degree of sustainable development among the three dimensions, the corporate sustainability index is used to express the overall sustainability performance of a company. A case study on the internal combustion engine manufacturing industry in China has been conducted to verify the validity and practicability of the proposed method. A questionnaire survey was conducted at 52 companies to collect the economic, environmental, and social indicators data during 2010–2012. A total of 49 companies responded, yielding a total of 103 economic samples, 102 social samples, and 79 environmental samples. The results of this investigation show that a large gap exist in the reported enterprises in their sustainability, and most of them are recommended to take measures to improve the sustainability performance. At the end, a specific company is selected to illustrate how to identify the strengths and weaknesses of its sustainability performance.